Recent advances and perspectives of ultrasound assisted membrane food processing - Córdova, Andrés; Astudillo-Castro, Carolina; Ruby-Figueroa, René; Valencia, Pedro; Soto, Carmen (Food research international, 2020)
[Display omitted] •Ultrasound assisted membrane food processing has not been properly reviewed yet.•Lack of standardization in experimental trials makes suitable comparisons impossible.•Dairy products are the most studied application of acoustic filtration in foods.•Research has been focused on flux enhancement without concern of quality issues.•Novel transducers with amplifiers will allow the scaling-up of these processes. Power ultrasound (US) transmits substantial amounts of small mechanical movements serving for particle detaching in membrane filtrations. This topic has been reviewed in recent years mainly focused on the mechanisms by which the flux is improved under specific processing conditions. US also been shown to improve food quality by changing physical properties and modifying the activity of enzymes and microorganisms. Surprisingly, limited information exists regarding on how the application of US results in terms of process and quality during membrane filtration of complex matrices such as liquid foods. This review highlights the recent advances in the use of US in membrane filtration processes focused in the manufacturing of foodstuffs and food ingredients, and perspectives of novel hybrid membrane-US systems that may be quite interesting for this field. The application of US in food membrane processing increases the flux, but the lack of standardization regarding to experimental conditions, make suitable comparisons impossible. In this sense, careful attention must be paid regarding to the ultrasonic intensity (UI), the membrane configuration and type of transducers and volume of the treated solution. Dairy products are the most studied application of US membrane food processing, but research has been mainly focused on flux enhancement; hitherto there have been no reports of how operational variables in these processes affect critical aspects such as quality and food safety. Also, studies performed at industrial scale and economical assessments are still missing. Application of US combined with membrane operations such as reverse osmosis (RO), forward osmosis (FO) and enzyme membrane bioreactors (EMBR) may result interesting for the production of value-added foods. In the perspective of the authors, the stagnation of the development of acoustic filtration systems in food is due more to a prejudice on this subject, rather than actual impedance due to the lack of technological development of transducers. This later has shown important advances in the last years making them suitable for tailor made applications, thus opening several research opportunities to the food engineering not yet explored.